IKATAN PUSTAKAWAN INDONESIA MENJAWAB TANTANGAN GLOBALISASI DAN OTONOMI DAERAH DALAM PENGEMBANGAN KEPUSTAKAWANAN - Dedi Junaedi (Ikatan Pustakawan Indonesia, 2015)
Librarian as the guardian of knowledge is a dynamic profession in management infomation and science analysis. Librarians face a dynamically changing environment, including globalization and economic liberalization as well as information and communication technology. Human resources between countries becomes a necessity, it means Indonesia will be filled by foreign workers, as well as librarians. Indonesian librarians are in a dilemma, between global competition and professional dedication as a bureaucrat Therefore, the Indonesian librarians should be the host. The key is professionalism, integrity, and competence. IPI as libmrianship organization should became the initiator and catalyst in responding to environmental changes, such as the development of science and technology, decentralization, reform, and the economic of ASEAN integration (MEA 2015). Furthermore, IPI must be a leading sector of professional libmrianship organization, independent, and based on the entrepreneurial leadership. The national strategy that must be done is strengthening partnerships, consolidation, and cooperation of professional organizations; strengthening quality of human resources in the library; increasing equality and welfare of librarians; strengthening development facilities of librarian standards in Indonesia; strengthening professional leadership.